Combined NK-CIK and PD-1 inhibitor (nivolumab), an effective immunotherapy for treating intrahepatic lymphoepithelioma-like cholangiocarcinoma unassociated with EBV infection: Two case reports and a literature review - Sam Saji, Alen; Yang, Biao; Hou, Wan Ting; Liu, Xia; Ren, Qiu Ping; Wei, Yuan Feng; Zhang, Yu Zu; Yang, Xi (Frontiers in Oncology, 2023)
Intrahepatic lymphoepithelioma-like cholangiocarcinoma (LELCC) is a very rare malignant tumor arising from the biliary epithelium. To date, there has been a lack of evidence on the radiographical features, clinicopathological features, and treatment modalities of LELCC, with less than 28 cases of LELCC without Epstein–Barr virus (EBV) infection having been reported worldwide. The treatment of LELCC remains unexplored. Here, we present two cases of patients with LELCC without EBV infection who were treated by liver resection, chemotherapy, and immunotherapy and who achieved long survival time. The patients received surgery to remove the tumors and then adjuvant chemotherapy using the GS regimen and combined immunotherapy involving natural killer–cytokine-induced killer (NK-CIK) and nivolumab were performed. Both patients had a good prognosis with a survival time of more than 100 months and 85 months.